2012
DOI: 10.1073/pnas.1116975109
|View full text |Cite
|
Sign up to set email alerts
|

Low-resolution solution structures of Munc18:Syntaxin protein complexes indicate an open binding mode driven by the Syntaxin N-peptide

Abstract: When nerve cells communicate, vesicles from one neuron fuse with the presynaptic membrane releasing chemicals that signal to the next. Similarly, when insulin binds its receptor on adipocytes or muscle, glucose transporter-4 vesicles fuse with the cell membrane, allowing glucose to be imported. These essential processes require the interaction of SNARE proteins on vesicle and cell membranes, as well as the enigmatic protein Munc18 that binds the SNARE protein Syntaxin. Here, we show that in solution the neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 46 publications
12
69
3
Order By: Relevance
“…This explanation accords with present models for SM interactions with several Qa-SNAREs (Rathore et al, 2010;Rizo and Südhof, 2012;Archbold et al, 2014). It is consistent, too, with recent studies of the yeast and mammalian SM proteins Sly1p (Demircioglu et al, 2014) and Munc18-1 (Christie et al, 2012), which appear to bind their cognate Qa-SNAREs concurrently via the major cleft and the N-terminal site on the SM protein. In the case of Sly1p, binding to the N-terminal site has been suggested to be important for forming a quasi-open or "loosened" conformation of the Qa-SNARE.…”
Section: Syp121 and Sec11 N Termini Mediate In Traffic Control At Thesupporting
confidence: 79%
“…This explanation accords with present models for SM interactions with several Qa-SNAREs (Rathore et al, 2010;Rizo and Südhof, 2012;Archbold et al, 2014). It is consistent, too, with recent studies of the yeast and mammalian SM proteins Sly1p (Demircioglu et al, 2014) and Munc18-1 (Christie et al, 2012), which appear to bind their cognate Qa-SNAREs concurrently via the major cleft and the N-terminal site on the SM protein. In the case of Sly1p, binding to the N-terminal site has been suggested to be important for forming a quasi-open or "loosened" conformation of the Qa-SNARE.…”
Section: Syp121 and Sec11 N Termini Mediate In Traffic Control At Thesupporting
confidence: 79%
“…Our data demonstrate that unlike Munc18-1, Munc18c binding to syntaxin does not block SNARE complex assembly or the fusion kinetics. When bound to Munc18c, syntaxin-4 adopts an open conformation fully competent for assembly with other SNARE subunits, in agreement with Munc18c structural and binding studies performed in solution (57,58). Therefore, the closed syntaxin binding mode is not conserved even among exocytic SM proteins.…”
Section: Munc18supporting
confidence: 59%
“…The structures of SNARE complexes are conserved across vesicle fusion pathways (72)(73)(74). Similarly, all SM proteins adopt a compact, arch-like configuration (34,35,58,75,76). However, the architecture of the SNARE/ SM complex appears to differ significantly across vesicle fusion pathways.…”
Section: Munc18mentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, a recent study has demonstrated that the crucial role of syntaxin N-peptide in monomeric interaction with Munc18 is isoform-dependent; deletion of N-peptide in syntaxin-1 has little effect on its binding to Munc18-1, whereas a similar deletion in syntaxin-4 dramatically reduces its binding with Munc18-3 (46). Mechanistically, we suggest that these two binding modes work together in chaperoning the cognate syntaxins in both neuronal and immune cell exocytosis; however, the relative contributions of these two binding modes vary depending on cell types.…”
Section: Discussionmentioning
confidence: 99%